Analytics: Sports Stats & More - Matt Marini
The biggest news in sports these days is the power of numbers. Stats have been around since sports began, but today, high-level math, computer savvy, and imaginative sports-lovers have created the active science of analytics. Teams at every level are looking for people with math skills who are also sports lovers. Can you turn your skills in math into a job in sports? Find out inside, and see if the numbers add up! If you want to stay in the game in any way you can, Careers Off the Field is for you. Every book shows you ways to combine your passion for sports with a way to make sports your career, even if youre not putting on a uniform. Each title in this series contains color photos, charts showing salaries for career areas, tips on key educational steps toward the career, and back matter including: an index, further reading lists for books and internet resources, and a series glossary.